2010
DOI: 10.4103/0974-7753.66919
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse neurofibroma of the scalp presenting as circumscribed alopecic patch

Abstract: Neurofibroma is a benign tumor of the peripheral nerve sheath characterized by proliferation of Schwann cells, perineural cells and endoneurial fibroblasts. Different types of neurofibromas can be identified, including localized, plexiform, and diffuse types. Diffuse neurofibroma is an uncommon form of neurofibroma that occurs primarily in children and young adults. The head and neck regions are the most common sites of involvement. Diffuse neurofibroma is an ill-defined infiltrative lesion and tends to involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“… 4 - 8 Intracranial extension of the extracranial variety of this tumor has rarely been reported 7 and malignant transformation is believed to be rare, however pain and enlargement may proclaim it. 2 Although Megahed and Hassel et al reported higher association rates, it is estimated that about 10% of these tumors are associated with NF 2 , 4 , 5 , 8 , 9 Some authors attribute the lower estimated incidence of NF-1 to the young age of patients with diffuse neurofibroma, which often precludes a reliable diagnosis of NF-1. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 4 - 8 Intracranial extension of the extracranial variety of this tumor has rarely been reported 7 and malignant transformation is believed to be rare, however pain and enlargement may proclaim it. 2 Although Megahed and Hassel et al reported higher association rates, it is estimated that about 10% of these tumors are associated with NF 2 , 4 , 5 , 8 , 9 Some authors attribute the lower estimated incidence of NF-1 to the young age of patients with diffuse neurofibroma, which often precludes a reliable diagnosis of NF-1. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Diffuse neurofibromas usually manifest as diffuse dermal plaque-like swellings in the head and neck regions resulting in enlargement of the affected tissue [ 7 ]. These are uncommon with less than 10% presenting as diffuse neurofibromas in neurofibromatosis type 1 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial extension of the extracranial variety of this tumor has rarely been described [4]. Although Kumar et al [5] reported higher association rates, it is estimated that about 10% of these tumors are associated with NF-1. On histopathological examination, diffuse NFs are ill-defined tumors that diffusely infiltrate the dermis and subcutaneous tissue, often extending along connective tissue septa, without destroying the normal structures.…”
Section: Discussionmentioning
confidence: 99%